The Value of Tumour Markers in the Detection of Relapse—Lessons Learned from the Swiss Austrian German Testicular Cancer Cohort Study - Stefanie Fischer; Christian Rothermundt; Odile Stalder; Angelika Terbuch; Thomas Hermanns; Deborah Zihler; Beat Müller; Christian D. Fankhauser; Anita Hirschi-Blickenstorfer; Bettina Seifert; Luis Alex Kluth; Mark-Peter Ufe; et al. (European Urology Open Science, 2023)
The tumour markers alpha-fetoprotein (AFP), beta human chorionic gonadotropin (βHCG), and lactate dehydrogenase (LDH) have established roles in the management and follow-up of testicular cancer. While a tumour marker rise can serve as an indicator of relapse, the frequency of false-positive marker events has not been studied systematically in larger cohorts. We assessed the validity of serum tumour markers for the detection of relapse in the Swiss Austrian German Testicular Cancer Cohort Study (SAG TCCS). This registry was set up to answer questions on the diagnostic performance and impact of imaging and laboratory tests in the management of testicular cancer, and has included 948 patients between January 2014 and July 2021.A total of 793 patients with a median follow-up of 29.0 mo were included. In total, 71 patients (8.9%) had a proven relapse, which was marker positive in 31 patients (43.6%). Of all patients, 124 (15.6%) had an event of a false-positive marker elevation. The positive predictive value (PPV) of the markers was limited, highest for βHCG (33.8%) and lowest for LDH (9.4%). PPV tended to increase with higher levels of elevation. These findings underline the limited accuracy of the conventional tumour markers to indicate or rule out a relapse. Especially, LDH as part of routine follow-up should be questioned. Patient summary: With the diagnosis of testicular cancer, the three tumour markers alpha-fetoprotein, beta human chorionic gonadotropin, and lactate dehydrogenase are routinely measured during follow-up to monitor for relapse. We demonstrate that these markers are often falsely elevated, and, by contrast, many patients do not have marker elevations despite a relapse. The results of this study can lead to improved use of these tumour markers during follow-up of testis cancer patients.